Winnie Childs, the Shop Girl - Williamson, C. N. (Charles Norris), 1859-1920; Williamson, A. M. (Alice Muriel), 1869-1933 (Salt Lake City, UT : Project Gutenberg, 2005)
"Winnie Childs, the Shop Girl" by C. N. Williamson and A. M. Williamson is a novel written in the early 20th century. The story follows the titular character, Winifred Child, a young woman who embarks on an adventurous journey across the Atlantic on the luxury liner "Monarchic". Throughout her experiences, she encounters a variety of fascinating characters, including Peter Rolls, a likable young man who becomes intrigued by her. The opening of the novel begins aboard the "Monarchic" during a dreadful storm at sea that has left most passengers feeling ill. While others succumb to seasickness, Peter Rolls remains unaffected and discovers a mysterious room that appears to be inhabited by five beautiful young women in elaborate evening gowns. Each of these girls, including Winifred, is a model for the renowned fashion designer Madame Nadine. As the storm continues, Peter becomes increasingly drawn to Winifred, whose humorous and unconventional perspective on life stands out among her more glamorous companions. The foundation is set for themes of romance and personal growth as Winifred transitions from the luxury of her former life into a new world full of opportunities and challenges in New York City. (This is an automatically generated summary.)
Release date is 2005-02-10
Produced by Ronald Holder and the Online Distributed Proofreading Team.
Keywords: New York (N.Y.) -- Fiction; Young women -- Fiction; Clerks (Retail trade) -- Fiction; Department stores -- Fiction